Alleles Contributing to ACCase-Resistance in an Italian Ryegrass (Lolium perenne ssp. multiflorum) Population from Oregon. Issue 3 (September 2014) - Martins, Bianca A. B.; Sánchez-Olguín, Elena; Perez-Jones, Alejandro; Hulting, Andrew G.; Mallory-Smith, Carol
Abstract : Acetyl-coenzyme A carboxylase (ACCase)–resistant Italian ryegrass is one of the most difficult-to-control weeds in United States wheat-production systems. Seed was collected from a suspected ACCase-resistant Italian ryegrass population in a winter wheat field with a history of ACCase-inhibitor herbicide use. This study investigated cross-resistance patterns in this Italian ryegrass population. Resistance was identified to the commercial dose of the ACCase herbicides pinoxaden, clethodim, sethoxydim, and clodinafop. Partial chloroplastic ACCase sequences revealed aspartate-to-glycine or isoleucine-to-asparagine substitutions at positions 2078 or 2041 in individuals of the resistant population. This is the first report, to our knowledge, of Asp-2078-Gly and Ile-2041-Asn substitutions in ACCase-resistant Italian ryegrass in the United States. Associating the occurrence of resistance alleles with resistance to specific active ingredients provides a better understanding of ACCase cross-resistance in Italian ryegrass and possibly options for its control.